Impact of pharmacist-supported transition of care services in the Middle East and North Africa: a systematic review and meta-analysis - Eman N. Alhmoud; Safa Farooq Fouad Alrawi; Rasha El-Enany; Mohamed Izham Mohamed Ibrahim; Muhammad Abdul Hadi (Taylor & Francis Group, 2024)
ABSTRACTBackground Transition of care (TOC) is associated with an increased risk of medication-related problems. Despite recent advancements in pharmacy practice and research in the Middle East and North Africa (MENA), the characteristics and impact of regional pharmacy-supported TOC interventions remain unclear.This systematic review and meta-analysis aimed to describe pharmacist-supported TOC interventions in the MENA region and evaluate their effectiveness.Methods PubMed, CINAHL, EMBASE, Web of Science, World Health Organization's International Clinical Trials Registry Platform (ICTRP) were searched from their inception to March 9, 2023, for experimental studies published in English, comparing pharmacist-supported TOC interventions with usual care for adults (age ≥18 years) discharged from the hospital. The risk of bias was evaluated using Cochrane's risk-of-bias tool for randomised trials (ROB2) and the risk of bias in non-randomised studies of interventions (ROBINS-I) tool for randomised and non-randomised studies respectively. Narrative syntheses and meta-analysis methods were employed depending on the outcomes evaluated.Results Twelve studies (n = 2377 subjects), 10 randomised controlled trials and 2 quasi-experimental studies, were included. Most studies had high or serious risk of bias. The included studies were quite heterogeneous in terms of nature and the delivery of intervention, and assessment of outcome measures. Compared to the usual care group, pharmacist-led TOC interventions contributed to a significant reduction in preventable drug-related (N = 2) and cardiac-related healthcare utilisation (N = 1), a significant reduction in preventable adverse drug events (ADEs) (Odds ratio (OR) 0.34, 95% CI: 0.13-0.94) and an improvement in medication adherence. However, all-cause hospitalisation and medication discrepancies were not significantly reduced.Conclusion Pharmacy-supported TOC interventions may improve patient outcomes in the MENA region. However, considering the limited quality of evidence and the variability in intervention delivery, future well-designed clinical trials are needed.